KELARUTAN PIGMEN ANORGANIK MERAH DAN BIRU DALAM GELASI MIKROEMULSI AIR DALAM MINYAK DARI SISTEM AIR, SURFAKTAN ANIONIK (SDS) DAN PENTANOL UNTUK TINTA BALLPOINT - Hardila, Yesi (Journal of Technique Research (JTR), 2019)
Red and blue inorganic pigments dissolve in the structure of the association of microemulsions and liquid crystals. This association structure can be used to make printer ink and ballpoint ink. The aim of this research was to prepare the gel from the water in oil microemulsion and determine and observe how the solubility of red and blue inorganic pigments in the gelation of microemulsion water in oil water systems, anionic surfactants (SDS) and pentanol. Gel preparation is done by the sol gel method. Sol gel is a process of adding inorganic compounds through chemical reactions in solutions at low temperatures. The resulting gel is half solid and has the ability to dissolve pigments more than microemulsions and liquid crystals. The solubility of red and blue pigments obtained on microemulsions is the red pigment 1.4 mg / g and the solubility of blue pigment 1.9 mg / g.